2011
DOI: 10.1186/1749-7922-6-18
|View full text |Cite
|
Sign up to set email alerts
|

Seatbelts and road traffic collision injuries

Abstract: Modification of seatbelts and their legislation played an important role in reducing morbidity and mortality of occupants in road traffic collisions. We aimed to review seatbelt development, its mechanism of action and its effects. Seatbelts reduce injury by preventing the occupant from hitting the interior parts of the vehicle or being ejected from the car. We have made a linear regression correlation between the overall seatbelt compliance and road traffic death rates in 46 high income countries to study the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
80
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 53 publications
2
80
2
2
Order By: Relevance
“…Although the improved availability, costeffectiveness, and speed of CT scans likely has contributed to this finding, we cannot be certain that this is the only driver of the increased incidence observed in our study. In other settings, trade-offs in MVC-related injuries were observed as new safety techniques allowed for increased survival [1,7,11] but no such trade-offs were observed in our study. As seatbelt and airbag technologies continue to improve, thoracolumbar injuries may be trade-offs for injuries to other anatomic regions not evaluated in our study.…”
Section: Discussioncontrasting
confidence: 68%
See 4 more Smart Citations
“…Although the improved availability, costeffectiveness, and speed of CT scans likely has contributed to this finding, we cannot be certain that this is the only driver of the increased incidence observed in our study. In other settings, trade-offs in MVC-related injuries were observed as new safety techniques allowed for increased survival [1,7,11] but no such trade-offs were observed in our study. As seatbelt and airbag technologies continue to improve, thoracolumbar injuries may be trade-offs for injuries to other anatomic regions not evaluated in our study.…”
Section: Discussioncontrasting
confidence: 68%
“…Increases in nonfatal injuries in exchange for decreases in more serious and fatal injuries have been seen in other settings [1,7,11]. In our study, however, no consistent compensatory decreasing trends were observed in sacropelvic injuries as a whole.…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations